Exploring direct and indirect targets of current antileishmanial drugs using a novel thermal proteomics profiling approach - Ibarra-Meneses, Ana Victoria; Corbeil, Audrey; Wagner, Victoria; Beaudry, Francis; do Monte-Neto, Rubens L.; Fernandez-Prada, Christopher (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis (VL), caused by Leishmania infantum, is an oft-fatal neglected tropical disease. In the absence of an effective vaccine, the control of leishmaniasis relies exclusively on chemotherapy. Due to the lack of established molecular/genetic markers denoting parasite resistance, clinical treatment failure is often used as an indicator. Antimony-based drugs have been the standard antileishmanial treatment for more than seven decades, leading to major drug resistance in certain regions. Likewise, drug resistance to miltefosine and amphotericin B continues to spread at alarming rates. In consequence, innovative approaches are needed to accelerate the identification of antimicrobial drug targets and resistance mechanisms. To this end, we have implemented a novel approach based on thermal proteome profiling (TPP) to further characterize the mode of action of antileishmanials antimony, miltefosine, and amphotericin B, as well as to better understand the mechanisms of drug resistance deployed by Leishmania. Proteins become more resistant to heat-induced denaturation when complexed with a ligand. In this way, we used multiplexed quantitative mass spectrometry-based proteomics to monitor the melting profile of thousands of expressed soluble proteins in WT, antimony-resistant, miltefosine-resistant, and amphotericin B-resistant L. infantum parasites, in the presence (or absence) of the above-mentioned drugs. Bioinformatics analyses were performed, including data normalization, melting profile fitting, and identification of proteins that underwent changes (fold change > 4) caused by complexation with a drug. Data are available on ProteomeXchange Consortium (http://www.proteomexchange.org) under identifier PXD034836. With this unique approach, we were able to narrow down the regions of the L. infantum proteome that interact with antimony, miltefosine, and amphotericin B; validating previously-identified and unveiling novel drug targets. Moreover, analyses revealed candidate proteins potentially involved in drug resistance. Interestingly, we detected thermal proximity coaggregation for several proteins belonging to the same metabolic pathway (i.e., tryparedoxin peroxidase and aspartate aminotransferase in proteins exposed to antimony), highlighting the importance of these pathways. Collectively, our results could serve as a jumping-off point for the future development of innovative diagnostic tools for the detection and evaluation of antimicrobial-resistant Leishmania populations, as well as open the door for new on-target therapies.